Adoption status and factors influencing adoption of livestock vaccination in India: An application of multinomial logit model - RATHOD, PRAKASH KUMAR; CHANDER, MAHESH (The Indian Journal of Animal Sciences, 2016)
The present study highlighted the efforts of government of India for livestock health and disease control, adoption status of livestock vaccination technology, constraints as perceived by farmers and identified factors affecting adoption of vaccination in India using multinomial logit model. The primary data from 360 dairy farmers of 4 states in North India and secondary data from various sources were used for this purpose. The adoption status revealed that majority of the respondents partially adopted vaccination for more than 9 years, followed by adoption since 6–9 years depicting a highly significant difference among the respondents across the states. Multinomial logit model depicted the Chi-square value of 110.05 which showed that likelihood ratio statistics are highly significant suggesting that model was fit for explanation. The variables ‘distance to veterinary institution’ or ‘animal healthcare centre’ and livestock holding were significantly associated with the probability that the respondent will be a full adopter of vaccination. The study suggested that researchers and extension experts need to make farmers more aware about the benefits of vaccination. Further, the scientists have to analyze the problems of dairy farmers and find suitable solutions for higher diffusion and adoption at field conditions by participatory technology generation and transfer approach.